1998
DOI: 10.1037/h0080345
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, gay, and bisexual youth and their families: Disclosure of sexual orientation and its consequences.

Abstract: Lesbian, gay, and bisexual youngsters, aged 14-21 and living at home, were studied for patterns of disclosure of sexual orientation to families. Three-quarters had told at least one parent, more often the mother than the father. Those who had disclosed were generally more open about their sexual orientation than those who had not, and few of the nondisclosed expected parental acceptance. Those who had disclosed reported verbal and physical abuse by family members, and acknowledged more suicidality than those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
398
3
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 531 publications
(431 citation statements)
references
References 25 publications
18
398
3
7
Order By: Relevance
“…The authors found that gender was important; fathers were more likely to react negatively to their child coming out than mothers, especially with gay sons, and fathers were less likely than mothers to be informed of their child's lesbian or gay identity altogether (Ben-Ari, 1995;Merighi & Grimes, 2000). Brothers also tended to react more negatively toward a gay sibling than sisters (D'Augelli, Hershberger, & Pilkington, 1998). Outside of familial dynamics, Costa and Davies (2012) found that lesbians were more positively regarded than gay men and that women in general were more likely than men to have positive attitudes toward lesbian, gay, bisexual, and transgender (LGBT) individuals.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The authors found that gender was important; fathers were more likely to react negatively to their child coming out than mothers, especially with gay sons, and fathers were less likely than mothers to be informed of their child's lesbian or gay identity altogether (Ben-Ari, 1995;Merighi & Grimes, 2000). Brothers also tended to react more negatively toward a gay sibling than sisters (D'Augelli, Hershberger, & Pilkington, 1998). Outside of familial dynamics, Costa and Davies (2012) found that lesbians were more positively regarded than gay men and that women in general were more likely than men to have positive attitudes toward lesbian, gay, bisexual, and transgender (LGBT) individuals.…”
mentioning
confidence: 93%
“…The siblings groups selected for the present comparative case analysis were chosen based on several principal variables that included gender of siblings (see D'Augelli et al, 1998) and birth order (see LaSala, 2010). Furthermore, these two cases were also chosen in response to the differences they presented in the realm of gender (group of brothers versus group of sisters) and race/ ethnicity, where Kevin was from a Romani family and Axelle was from a White family (Table 1).…”
Section: Participantsmentioning
confidence: 99%
“…They are at risk for harassment and discrimination (Hetrick & Martin, 1987;Martin & Hetrick, 1988), victimization (Hershberger & D'Augelli, 1995;Pilkington & D'Augelli, 1995), mental health and behavioral problems (Elze, 2002;Gonsiorek, 1988;Remafedi, 1987;Remafedi, Farrow, & Deisher, 1991;Rothblum, 1990;RotheramBorus, Rosario, Rossem, Heid, & Gillis, 1995), suicide ideation and attempts (Yoder, Hoyt, & Whitbeck, 1998), substance abuse (Rosario, Hunter, & Gwadz, 1997;Travers & Schneider, 1996), suicide (D'Augelli & Hershberger, 1993;Fergusson, Horwood, & Beautrais, 1999;Morrison & L'Heureaux, 2001;Rotheram-Borus & Hunter, 1994), and family troubles including physical and sexual abuse (Boxer et al, 1993;D'Augelli, Hershberger, & Pilkington, 1998;Savin-Williams & Rodriquez, 1993). As a consequence of these risk factors, there appear to be a disproportionate number of GLB adolescents in runaway populations (Remafedi, 1987).…”
Section: Victimization Of Glb Adolescentsmentioning
confidence: 99%
“…In this regard, homosexuality is still widely stigmatized despite greater acceptance evident in recent opinion polls of the American population (Butler, 2001). Lesbians and gay men commonly report positive histories of victimization and discrimination (Herek, Gillis, & Cogan, 1999;Hershberger & D'Augelli, 1995;Krieger & Sidney, 1997), particularly in adolescence or young adulthood (D'Augelli, Hershberger, & Pilkington, 1998;Lock & Steiner, 1999). As a consequence, homosexuality may be a risk indicator for higher rates of psychological distress and some mental disorders.…”
mentioning
confidence: 99%